Pengembangan Ekonomi Kreatif Batik Tulis Pamekasan Upaya Peningkatan Ekonomi Masyakat Persepektif Ekonomi Islam - Maulidi, Maulidi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The development of the creative economy has an important role in the development of the community's economy in the field of cultural heritage-based crafts, namely written batik. The biggest challenge for batik artisans in the current era is that we must maintain the preservation of a work so that it is not inferior to other batik industries. Because as time went on, Pamekasan written batik was getting thinner due to the rise of printing batik starting to be marketed considering that printing batik was cheaper in terms of price and production was more practical. Therefore, empowering the creative economy is capable of providing change through training and this training is an effort to empower the creative economy in Pamekasan district, especially in the Proppo and Palegaan sub-districts to improve the community's economy. This research used field research. The purpose of this research is to find out the extent of people's understanding of the creative economy, the majority of which are batik artisans. The method used in this research is qualitative, with the following data collection tools: interviews, observation and documentation. From this research Pamekasan district can increase people's income by using sharia principles, in addition to the program provided by the district government through the sub-district so that it can add insight and experience to participants who take part in the training. There were 15 people who took part in the training program and all implemented it in terms of batik management and also the use of social media.